Mortality statistics 1933 : thirty-fourth anual report - Great Britain. Office of Population Censuses and Surveys (London : Washington, 1936)
"Review of the Registrar General on deaths in England and Wales."
Merged with: Mortality statistics. Perinatal and infant, to form: Mortality statistics. Childhood, infant, and perinatal.
Keywords: Infants -- Great Britain -- Mortality -- Statistics -- Periodicals; Children -- Great Britain -- Mortality -- Statistics -- Periodicals; Death -- in infancy & childhood -- England -- statistics; Death -- in infancy & childhood -- Wales -- statistics; Infant Mortality -- England; Infant Mortality -- Wales; Great Britain -- Statistics, Vital -- Periodicals